Canopy structure, behavioral and physiological aspects of pasture-finished sheep using castor bean cake as alternative input - A.J.G. Meneses; R.P.F.F. Pompeu; H.O. Salles; A.S.S. Farias; L.H.S. Nenem; C.S. Costa; L.F. Guedes; J.S. Maranguape; P.L. Pereira; M.J.D. Cândido (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2024)
ABSTRACT The purpose was to evaluate structural characteristics of pasture, behavioral aspects and physiological parameters of sheep finished on irrigated Tamani grass pasture under continuous stocking, using castor bean cake as alternative input. Structural characteristics of the pasture were assessed in a randomized block design in 2 x 2 factorial arrangement, with two sources of nitrogen fertilization (mineral - urea and organic - in natura castor bean cake) and two supplements (with or without detoxified castor bean cake), in four replications (paddocks). Behavioral aspects and physiological parameters were assessed in a randomized block design with four treatments, and repeated measures over time in eight replications (sheep). Total forage biomass, green leaf blade biomass, grazing, rumination, and idleness times, as well as respiratory rate and rectal temperature were assessed. Urea provided greater leaf blade biomass (1,807 kg DM.ha.cycle-1) and tiller population density (1,592 tillers.m-2). Grazing time reduced 65 minutes.day-1 for animals supplemented with detoxified castor bean cake and kept in pastures fertilized with urea. The use of castor bean cake did not change the physiological parameters of the animals in any of the managements evaluated and can be used as a strategic input in the finishing of sheep on pasture.